The Relevance of Information and Communication Technology in Teaching of English Literature for both Pleasure And Education - Kaul, P; Kaur, J (International Journal of Computer Sciences and Engineering, 2025)
This paper aims to highlight the immense capacity of the use of Information and communication technology for the teaching of English literature. In the time of fast digitalization, one wonders why should the teaching of a traditional subject like English literature by use of digital methods be left behind when these digital tools are an intrinsic part of teaching technical subjects like engineering and other applied sciences. This paper throws some light on the practical relevance of the use of various tools of information and communication technology in classroom teaching the otherwise passive classroom teaching of literature can be instantly transformed to an active and live experience by extensive use of these tools. Increased use of information and communication technology will help in better understanding and lively exchange of information in the otherwise repetitive and prosaic traditional teaching methodology this paper proposes to use information and communication technology by digital aids like online educational videos, 3D Animation, Films, interactive media, language labs, e-libraries and various other browsers. The aim is not the replacement of the teacher but to supplement the teacher in order to reinforce and enhance traditional methods of teaching English literature.